2022
DOI: 10.1093/cid/ciac273
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Effect on Hepatitis C Elimination Among Men Who Have Sex With Men in the Swiss HIV Cohort Study: A Systematic Re-Screening for Hepatitis C RNA Two Years Following a Nation-Wide Elimination Program

Abstract: Introduction The Swiss HCVree Trial (NCT 02785666) was conducted in 2015-2017 with the goal of implementing a population-based systematic hepatitis C (HCV) micro-elimination program among men who have sex with men (MSM) living with HIV enrolled in the Swiss HIV Cohort Study (SHCS). The trial led to a 91% and 77% decline of HCV prevalence and incidence, respectively. The long-term effect of this HCV micro-elimination program is yet to be explored. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Evaluations of incidence rates of primary HCV infection and HCV reinfection have been performed in a number of other locales, mostly in Europe and Australia, before and after restrictions on prescribing of DAA were similarly lifted, with mixed findings. For primary infection, some locales found little or no decline in rates, similar to the report from Chromy and colleagues in Vienna 9,10 and some locales found greater reductions in rates but measured only in the short term, 11–14 and in Switzerland, a longer‐term reduction was found, over a period of two years 14 . For reinfections, which are a better measure of elimination efforts as they occur among those who are part of sexual networks with high HCV prevalence and participate in behaviours that mediate HCV transmission, most locales found little or no decline in rates, 9,11,14–16 with the exception of a short‐term decline in the Netherlands 13 …”
supporting
confidence: 76%
See 1 more Smart Citation
“…Evaluations of incidence rates of primary HCV infection and HCV reinfection have been performed in a number of other locales, mostly in Europe and Australia, before and after restrictions on prescribing of DAA were similarly lifted, with mixed findings. For primary infection, some locales found little or no decline in rates, similar to the report from Chromy and colleagues in Vienna 9,10 and some locales found greater reductions in rates but measured only in the short term, 11–14 and in Switzerland, a longer‐term reduction was found, over a period of two years 14 . For reinfections, which are a better measure of elimination efforts as they occur among those who are part of sexual networks with high HCV prevalence and participate in behaviours that mediate HCV transmission, most locales found little or no decline in rates, 9,11,14–16 with the exception of a short‐term decline in the Netherlands 13 …”
supporting
confidence: 76%
“…For primary infection, some locales found little or no decline in rates, similar to the report from Chromy and colleagues in Vienna 9,10 and some locales found greater reductions in rates but measured only in the short term, [11][12][13][14] and in Switzerland, a longerterm reduction was found, over a period of two years. 14 For reinfections, which are a better measure of elimination efforts as they occur among those who are part of sexual networks with high HCV prevalence and participate in behaviours that mediate HCV transmission, most locales found little or no decline in rates, 9,11,[14][15][16] with the exception of a short-term decline in the Netherlands. 13 The lack of significant decline in primary infection rates in some…”
supporting
confidence: 68%
“…Evidence from cohorts of PLHIV in high-income countries have shown decreases in primary HCV incidence in recent years, particularly after DAA introduction. [14][15][16][17][18][19][20] However, in some countries, primary incidence was declining before DAA introduction, or trends in incidence have only been analysed during the DAA era. Therefore, it is unclear whether observed incidence reductions would have occurred even without DAAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is reason to believe that our conclusions regarding the efficiency of risk reduction strategies will apply to other high-income settings with similar HCV epidemics among MSM (i.e. decreasing incidence [46][47][48]). Engagement in chemsex and other high-risk sexual practices substantially contributes to HCV transmission among MSM living with HIV in all settings, and a number of modelling studies have shown that micro-elimination cannot be achieved without implementing risk reduction interventions [15,49,50].…”
Section: Discussionmentioning
confidence: 99%